Using Social Media to Promote International Collaboration - Hua Sun; Mark Douglas Puterbaugh (Pennsylvania Libraries: Research & Practice, 2013)
This paper explores the use of social media or Web 2.0 services for an international collaborative project. Participants in this collaboration used free and inexpensive social media tools to communicate and work together. This case study presents a model for using inexpensive social media tools to forge new partnerships among academic libraries. Academic libraries can now tap the expertise of fellow librarians in other countries and explore new cultures to improve and extend their services without the huge financial cost once attributed to international collaboration.